FPGA-Based Implementation of a New Phase-to-Sine Amplitude Conversion Architecture - Omran, Q. K.; Islam, M. T.; Misran, N. (Elektronika ir Elektrotechnika, 2013)
The classical structure of linear interpolation-based phase-to-sine mapper (PSM) consists of at least two ROMs for polynomial coefficient storage. Other architectures may include extra ROM for storing residual errors. However, ROMs dissipate high power and occupy a significant amount of the die area. This study presents a new technique that eliminates the ROM by including the computation of segment initial coefficients in the hardware. Therefore, it becomes possible to trim down noticeable hardware resources. The proposed direct digital frequency synthesizer (DDFS) architecture has been encoded in VHDL and synthesized with Quartus II software. Post simulation results show that the proposed design is capable of achieving the theoretical spurious-free dynamic range (SFDR) upper bound when optimal polynomial coefficients are considered. For 32 piecewise linear segments, the SFDR of the synthesized sinusoid is 84.15 dBc. A ROM compression ratio of 597.3:1 was also achieved. The performance of the DDFS is compared with previously presented DDFS techniques and the results show that the proposed design has advantages of high ROM compression ratio and low hardware complexity. DOI: http://dx.doi.org/10.5755/j01.eee.19.10.5905